Polygamy slows down population divergence in shorebirds. (10th April 2017) - D'Urban Jackson, Josephine; dos Remedios, Natalie; Maher, Kathryn H.; Zefania, Sama; Haig, Susan; Oyler‐McCance, Sara; Blomqvist, Donald; Burke, Terry; Bruford, Michael W.; Székely, Tamás; Küpper, Clemens
Abstract : Sexual selection may act as a promotor of speciation since divergent mate choice and competition for mates can rapidly lead to reproductive isolation. Alternatively, sexual selection may also retard speciation since polygamous individuals can access additional mates by increased breeding dispersal. High breeding dispersal should hence increase gene flow and reduce diversification in polygamous species. Here, we test how polygamy predicts diversification in shorebirds using genetic differentiation and subspecies richness as proxies for population divergence. Examining microsatellite data from 79 populations in 10 plover species (Genus: Charadrius ) we found that polygamous species display significantly less genetic structure and weaker isolation‐by‐distance effects than monogamous species. Consistent with this result, a comparative analysis including 136 shorebird species showed significantly fewer subspecies for polygamous than for monogamous species. By contrast, migratory behavior neither predicted genetic differentiation nor subspecies richness. Taken together, our results suggest that dispersal associated with polygamy may facilitate gene flow and limit population divergence. Therefore, intense sexual selection, as occurs in polygamous species, may act as a brake rather than an engine of speciation in shorebirds. We discuss alternative explanations for these results and call for further studies to understand the relationships between sexual selection, dispersal, and diversification.